Corporate governance and cost of equity capital: the mediation role of accounting conservatism - Widiatmoko, Jacobus; Indarti, Maria Goretti Kentris (Journal of Accounting and Investment, 2024)
Research aims: This study examines the effect of corporate governance as proxied by institutional and managerial ownership and profitability on the cost of equity capital, both directly and indirectly, through accounting conservatism as a mediating variable.Design/Methodology/Approach: The population of this study was manufacturing companies listed on the Indonesia Stock Exchange in 2020–2022. The sample selection was carried out using the purposive sampling method, resulting in 230 data points and then tested using multiple linear regression.Research findings: Institutional ownership and profitability were revealed to have a positive influence on accounting conservatism, while managerial ownership had no influence. Profitability and accounting conservatism exerted a negative effect on the cost of equity capital. However, institutional ownership generated a positive effect, but managerial ownership did not affect the cost of equity capital. Further test results uncovered that the impact of institutional ownership and profitability on the cost of equity capital was mediated by accounting conservatism.Theoretical contribution/Originality: The findings of this research enrich previous research regarding the economic consequences of corporate governance, profitability, and accounting conservatism in equity markets in developing countries, especially Indonesia.Practitioner/Policy implication: The results of this research can be used as consideration for investors in developing country capital markets when making investment decisions.Research limitation/Implication: This research has limitations, including the relatively low adjusted R2 value. Proxies for corporate governance from ownership and board structure should be included in future studies.